O contrato de trabalho intermitente à luz do conceito de trabalho decente da Organização Internacional do Trabalho - Medeiros, Maria Eduarda Moreira de (2024)
The introduction of the intermittent hiring regime in Brazil, through the Labor Reform, Law No. 13,467/2017, was justified by the belief that the high levels of informality and unemployment in the country were due, in large part, to the limitations of the conventional hiring model. work. However, there are concerns regarding the compatibility of this new system with the constitutional and conventional legal order that has been established in the country, and whether it will actually achieve the objectives it set out to achieve. This dissertation aims to explore the importance of the obstacles faced in the implementation of this new model, from the perspective of guaranteeing decent work as conceptualized by the ILO